Gender and Mobility in Africa Borders, Bodies and Boundaries (Springer International Publishing, 2018)
This volume examines gender and mobility in Africa though the central themes of borders, bodies and identity. It explores perceptions and engagements around 'borders'; the ways in which 'bodies' and women's bodies in particular, shape and are affected by mobility, and the making and reproduction of actual and perceived 'boundaries'; in relation to gender norms and gendered identify. Over fourteen original chapters it makes revealing contributions to the field of migration and gender studies. Combining historical and contemporary perspectives on mobility in Africa, this project contextualises migration within a broad historical framework, creating a conceptual and narrative framework that resists post-colonial boundaries of thought on the subject matter. This multidisciplinary work uses divergent methodologies including ethnography, archival data collection, life histories and narratives and multi-country survey level data and engages with a range of conceptual frameworks to examine the complex forms and outcomes of mobility on the continent today. Contributions include a range of case studies from across the continent, which relate either conceptually or methodologically to the central question of gender identity and relations within migratory frameworks in Africa. This book will appeal to researchers and scholars of politics, history, anthropology, sociology and international relations.